Functional conservation of Nematostella Wnts in canonical and noncanonical Wnt-signaling - Rigo Watermeier, Teresa; Ritthaler, Martin; Holstein, Thomas W. (Biology open, 2012)
Skip to Next Section Cnidarians surprise by the completeness of Wnt gene subfamilies (11) expressed in an overlapping pattern along the anterior-posterior axis. While the functional conservation of canonical Wnt-signaling components in cnidarian gastrulation and organizer formation is evident, a role of Nematostella Wnts in noncanonical Wnt-signaling has not been shown so far. In Xenopus, noncanonical Wnt-5a/Ror2 and Wnt-11 (PCP) signaling are distinguishable by different morphant phenotypes. They differ in PAPC regulation, cell polarization, cell protrusion formation, and the so far not reported reorientation of the microtubules. Based on these readouts, we investigated the evolutionary conservation of Wnt-11 and Wnt-5a function in rescue experiments with Nematostella orthologs and Xenopus morphants. Our results revealed that NvWnt-5 and -11 exhibited distinct noncanonical Wnt activities by disturbing convergent extension movements. However, NvWnt-5 rescued XWnt-11 and NvWnt-11 specifically XWnt-5a depleted embryos. This unexpected ‘inverse’ activity suggests that specific structures in Wnt ligands are important for receptor complex recognition in Wnt-signaling. Although we can only speculate on the identity of the underlying recognition motifs, it is likely that these crucial structural features have already been established in the common ancestor of cnidarians and vertebrates and were conserved throughout metazoan evolution.